75 GHz germanium waveguide photodetector with 64 Gbps data rates utilizing an inductive-gain-peaking technique. (1st January 2023) - Li, Xiuli; Zhu, Yupeng; Liu, Zhi; Peng, Linzhi; Liu, Xiangquan; Niu, Chaoqun; Zheng, Jun; Zuo, Yuhua; Cheng, Buwen
Abstract: High-performance germanium (Ge) waveguide photodetectors are designed and fabricated utilizing the inductive-gain-peaking technique. With the appropriate integrated inductors, the 3-dB bandwidth of photodetectors is significantly improved owing to the inductive-gain-peaking effect without any compromises to the dark current and optical responsivity. Measured 3-dB bandwidth up to 75 GHz is realized and clear open eye diagrams at 64 Gbps are observed. In this work, the relationship between the frequency response and large signal transmission characteristics on the integrated inductors of Ge waveguide photodetectors is investigated, which indicates the high-speed performance of photodetectors using the inductive-gain-peaking technique.